INDONESIA’S CONTRIBUTION OF DISPATCH THE NATIONAL POLICE AS A PEACEKEEPING OPERATIONS IN THE CENTRAL AFRICAN REPUBLIC IN 2019 - Faudina, Tasya; Nurhadi, Robi (Journal of Social Political Sciences, 2022)
This study expects to depict and dissect the job of Indonesia's investment in MINUSCA in the 2019 period. Where, Indonesia is in the main ten as a shipper of Peacekeeping soldiers and police. Thus, in this study there is a research question in the form of "Why is Indonesia involved in the effort to send the Indonesian National Police as a peacekeeping force in the Central African Republic for the 2019 period?". As the main organization, the United Nations carries out its task of ending the divisions that occur in the Central African Republic by establishing a special peacekeeping mission. As one of its member countries, Indonesia contributes fully and actively in carrying out world peace missions as one of the sending countries for peacekeeping troops. In this study uses a descriptive qualitative method which aims to describe the phenomena regarding the role of the United Nations and Indonesia's contribution to the mission in the Central African Republic. By using literature-based and internet-based methods with regard to linking the problems studied. The results of this study indicate the relationship with the role of Indonesia as a sending country for peacekeepers analyzed with the concept of Humanitarian Intervention, as well as Indonesia's interests in its participation.